2017
DOI: 10.1007/s11547-017-0824-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intensity modulated radiotherapy with simultaneous integrated boost (IMRT-SIB) and a 3-dimensional conformal parotid gland-sparing radiotherapy (ConPas 3D-CRT) in treatment of nasopharyngeal carcinoma: a mono-institutional experience

Abstract: IMRT-SIB provided additional spearing to parotid glands and spinal cord in comparison to ConPas 3D-CRT technique but without improvement of OS and DFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, 5-year disease-specific survival rates were 81% in the CRT group and 85% in the IMRT group, while the corresponding neurological toxicity rates were 3.5% and 1.8%. However, Bisof et al [11] conducted a retrospective study to compare IMRT and CRT in the treatment of NPC with regard to outcomes and dose distribution to the planning target volumes and to the organs at risk. Results showed that the mean dose and dose to 50% parotid glands volume as well as the maximal dose to the spinal cord were significantly lower in the IMRT group than in the CRT group.…”
Section: Discussionmentioning
confidence: 99%
“…However, 5-year disease-specific survival rates were 81% in the CRT group and 85% in the IMRT group, while the corresponding neurological toxicity rates were 3.5% and 1.8%. However, Bisof et al [11] conducted a retrospective study to compare IMRT and CRT in the treatment of NPC with regard to outcomes and dose distribution to the planning target volumes and to the organs at risk. Results showed that the mean dose and dose to 50% parotid glands volume as well as the maximal dose to the spinal cord were significantly lower in the IMRT group than in the CRT group.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized studies in adults have reported a clear clinical benefit (in terms of survival and quality of life) for image‐guided radiotherapy (IGRT) and IMRT/volumetric modulated arc therapy (VMAT) compared to 2D‐ or even 3D‐conformal radiation therapy 92–95 . Several reports in childhood are also in favor of IGRT and IMRT/VMAT use for NPC treatment, with decreased rates of acute and late toxicities and a better survival 2,96,97 .…”
Section: Radiotherapy Techniquesmentioning
confidence: 99%
“…Randomized studies in adults have reported a clear clinical benefit (in terms of survival and quality of life) for image-guided radiotherapy (IGRT) and IMRT/volumetric modulated arc therapy (VMAT) compared to 2D-or even 3D-conformal radiation therapy. [92][93][94][95] Several reports in childhood are also in favor of IGRT and IMRT/VMAT use for NPC treatment, with decreased rates of acute and late toxicities and a better survival. 6,15,92,97,102 We recommend patients undergo audiometry studies and hearing evaluation, dental examination and endocrinology evaluation every 6 months for 36 months following treatment, and yearly thereafter (Level IV; Grade B).…”
Section: Radiotherapy Techniquesmentioning
confidence: 99%
“…Intensity-modulated radiotherapy (IMRT) has been associated with a reduced toxicity profile in several head and neck tumors both in the curative and postoperative settings. However, its impact in SG cancer is currently supported by limited data [ 13 , 14 , 15 , 16 ]. The introduction of IMRT, as well as the addition of concurrent chemotherapy, has been associated with improved oncological outcomes in Dutch patients treated with chemoradiation for SG tumors [ 17 ].…”
Section: Introductionmentioning
confidence: 99%